Barriers in the Uptake and Delivery of Preconception Care: Exploring the Views of Care Providers - M’hamdi, Hafez Ismaili (Matern Child Health J, 2016)
Objectives To examine health care professionals’ views of their role and responsibilities in providing preconception care and identify barriers that affect the delivery and uptake of preconception care. Methods Twenty health care professionals who provide preconception care on a regular basis were interviewed using semi-structured interviews. Results We interviewed twelve community midwives, three General Practitioners, three obstetricians, one cardiologist specialized in congenital heart diseases and one gastroenterologist.We identified four barriers affecting the uptake and delivery of preconception care (PCC): (1) lack of a comprehensive preconception care program; (2) limited awareness of most future parents about the benefits of preconception care, hesitance of GP’s about the necessity and effectiveness of PCC; (3) poor coordination and organization of preconception care; (4) conflicting views of health care professionals on pregnancy, reproductive autonomy of patients and professional responsibility. Conclusion We have identified four barriers in the uptake and delivery of preconception care. Our findings support the timely implementation of a comprehensive program of PCC (already advocated by the Health Council of the Netherlands) and increasing awareness and knowledge of PCC from care providers and future parents. We emphasize the need for further research on how organizational barriers lead to suboptimal PCC and how interdisciplinary collaboration and referral can lead to optimally tailored intervention approaches. ELECTRONIC SUPPLEMENTARY MATERIAL: The online version of this article (doi:10.1007/s10995-016-2089-7) contains supplementary material, which is available to authorized users.